Examining the association between diabetes, depressive symptoms, and suicidal ideation among Aboriginal Canadian peoples living off-reserve: a cross-sectional, population-based study - Elamoshy R (Dove Medical Press, 2018)
Rasha Elamoshy,1 Yelena Bird,1 Lilian Ulrica Thorpe,2 John Moraros1 1School of Public Health, University of Saskatchewan, Saskatoon, SK, Canada; 2Community Health and Epidemiology Department, University of Saskatchewan, Saskatoon, SK, Canada Background: Diabetes is a prevalent chronic condition that has been linked to depression and suicidal behavior. The Aboriginal peoples of Canada are known to suffer from significant health disparities and higher burden of physical and mental illnesses. The purpose of this study was to assess whether diabetes is associated with higher depressive symptoms and lifetime suicidal ideation among Aboriginal Canadian peoples living off-reserve.Methods: Data were obtained from the Aboriginal Peoples Survey, 2012. Depressive symptoms were evaluated by a modified version of the previously validated K-10 scale, while diabetes and suicidal ideation were self-reported. A secondary analysis was conducted on a weighted sample of 689,860 participants for depressive symptoms (9.25% diabetics) and 694,960 for suicidal ideation (9.39% diabetics). Descriptive statistics and multiple logistic regression analysis were conducted.Results: Our study found that the prevalence of depressive symptoms was higher among diabetics (17.53%) compared with nondiabetics (11.12%; OR =1.70, 95% CI: 1.22–1.61). After adjusting for sociodemographic variables, smoking/alcohol use/drug use, anxiety disorders, and other chronic illnesses, diabetes was still significantly associated with depressive symptoms (aOR =1.46, 95% CI: 1.03–2.07). Additionally, diabetics (23.86%) were more likely to report suicidal ideation compared with nondiabetics (18.71%; OR =1.36, 95% CI: 1.05–1.77). Controlling for the effect of sociodemographics and health-related behaviors, diabetes was still associated with higher risk of reporting suicidal ideation (aOR =1.40, 95% CI: 1.05–1.88).Conclusion: Our results suggest that the Aboriginal Canadian diabetic patients living off-reserve are at higher risk of depressive symptoms and suicidal ideation. Culturally appropriate co-screening strategies need to be implemented in primary health care settings to provide the supports necessary for this vulnerable population. Further research is needed to fully elucidate the nature of these associations in order to develop effective intervention and treatment approaches. Keywords: aboriginal, Canada, diabetes, depression, depressive symptoms, suicidal ideation